La Crosse Encephalitis - Jorge R. Rey (EDIS)
La Crosse encephalitis is a relatively rare viral disease that is spread by infected mosquitoes. The disease affects the central nervous system and can be serious and even lethal in rare instances. It is named for the city of La Crosse, Wisconsin, where it was first identified in 1963. Since then, La Crosse encephalitis has been identified in several Midwestern and Mid-Atlantic states. This document is ENY672, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 2002.